Extraordinary NO2 Removal by the Metal–Organic Framework UiO‐66‐NH2. (13th April 2016) - Peterson, Gregory W.; Mahle, John J.; DeCoste, Jared B.; Gordon, Wesley O.; Rossin, Joseph A.
Abstract: Here we discuss the removal of nitrogen dioxide, an important toxic industrial chemical and pollutant, from air using the MOF UiO‐66‐NH2 . The amine group is found to substantially aid in the removal, resulting in unprecedented removal capacities upwards of 1.4 g of NO2 /g of MOF. Furthermore, whereas NO2 typically generates substantial quantities of NO on sorbents, the amount generated by UiO‐66‐NH2 is significantly reduced. Of particular significance is the formation of a diazonium ion on the aromatic ring of the MOF, and the potential reduction of NO2 to molecular nitrogen.